The Influence of Price Perception and Customer Satisfaction on The Performance of Pertamina Gas Stations Mediated By Service Quality (Empirical Study: Pertamina Gas Station Consumers In Jakarta) - Nie, Le; Bambang Sugiyanto, Liem (Pelopor Publikasi Akademika, 2025)
This study aims to analyze the influence of price perception and customer satisfaction on the performance of Pertamina gas station (SPBU), with service quality as a mediating variabel. The study focuses on Pertamina gas station customers in Jakarta, considering the city’s strategic role as an economic hub that significantly impacts national energy demand. A quantitative approach was employed, collecting data through questionnaires distributed to a randomly selected sample of customers. The independent variables in this study are price perception and customer satisfaction, while the dependent variable is gas station performance. Swervice quality acts as the mediating variable, measured through dimensions such as reliability, responsiveness, assuarance, empathy and tangibles. The collected data were analyzed using the structural Equation Modelling (SEM) method. The findings reveal that price perception has a positive and significant influence on customer satisfaction and service quality. Furthermore, customer satisfaction positively impacts gas station performance. Service quality was found to play a significant mediating role in the raltionship between price perception, customer satisfaction, and gas station performance. This indicates that enhancing service quality can strengthen the relationship between price perception and customer satisfaction on overall gas station performance. This study offers managerial implications for Pertamina, suggesting a focus on maintaining competitive price perception and improving service quality to enhance customer satisfaction and operational performance of gas stations. Additionally, it provides new insights in to the strategic importance of service quality in the competitive energy industry.